Exploring Potential Archaeological Expressions of Nonbinary Gender in Pre-Contact Inuit Contexts - Walley, Meghan (Études Inuit Studies, 2018)
In recent years, gender has factored heavily into the study of Inuit archaeological remains. Frequently, archaeologists have used diagnostic men’s and women’s tools to “see” gender in the archaeological record. However, recent anthropological literature attests to the existence of nonbinary gender categories in Inuit tradition. While the concept of nonbinary gender is not new in anthropological literature, it has not commonly been translated into meaningful archaeological research. Although many archaeologists studying Inuit gender have acknowledged the possibility of Inuit gender fluidity, virtually no archaeological research has directly addressed Inuit nonbinary gender. In this article, I discuss the anthropological concept of nonbinary gender and its diversity within Inuit culture, and then propose a variety of ways in which archaeologists conducting research on pre-contact Inuit gender might begin to study sites and materials within an interpretive framework that is more inclusive of these gender categories. These approaches include examination of artifacts, studies of the spatial distribution of sites, and re-examination of mortuary data. Through this work, I emphasize that gender occurs as a complex system rather than as two or three distinct sets of static social roles and that archaeologists need to adjust our approaches to past genders in order to see them through a culturally specific and meaningful lens.